2016
DOI: 10.1016/j.celrep.2016.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Slack K+ Channels Alters Mass at the Plasma Membrane by Triggering Dissociation of a Phosphatase-Regulatory Complex

Abstract: Summary Human mutations in the cytoplasmic C-terminal domain of Slack sodium-activated potassium (KNa) channels result in childhood epilepsy with severe intellectual disability. Slack currents can be increased by pharmacological activators or by phosphorylation of a Slack C-terminal residue by protein kinase C. Using an optical biosensor assay, we find that Slack channel stimulation in neurons or transfected cells produces loss of mass near the plasma membrane. Slack mutants associated with intellectual disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 32 publications
(50 reference statements)
2
61
0
Order By: Relevance
“…11,42 For some of the disease-causing mutations, it has been shown that they behave as channels that are constitutively phosphorylated at this site. 4,44,45 Thus far, however, only for Phactr1 is there direct evidence that these interactions are altered in disease-causing Slack mutant channels. 5,43 In addition to Phactr1, a number of other proteins have been identified as Slack-interacting binding partners of Slack channels including FMRP, PSD95, CYFIP1, and TMEM16C.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11,42 For some of the disease-causing mutations, it has been shown that they behave as channels that are constitutively phosphorylated at this site. 4,44,45 Thus far, however, only for Phactr1 is there direct evidence that these interactions are altered in disease-causing Slack mutant channels. 5,43 In addition to Phactr1, a number of other proteins have been identified as Slack-interacting binding partners of Slack channels including FMRP, PSD95, CYFIP1, and TMEM16C.…”
Section: Discussionmentioning
confidence: 99%
“…11 One of the mechanisms that has been proposed to explain how mutations lead to neuronal dysfunction is an alteration in the interactions of Slack channels with its cytoplasmic binding partners. 4 This protein is a member of the phosphatase and actin regulator family of proteins, which are highly expressed in the central nervous system and at lower levels also in heart, lung, kidney, and testis. 4,44,45 Thus far, however, only for Phactr1 is there direct evidence that these interactions are altered in disease-causing Slack mutant channels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations